Development of the Short Critical Consciousness Scale (ShoCCS). Issue 3 (3rd July 2022) - Diemer, Matthew A.; Frisby, Michael B.; Pinedo, Andres; Bardelli, Emanuele; Elliot, Erin; Harris, Elise; McAlister, Sara; Voight, Adam M.
Abstract: Critical consciousness represents the analysis and critique of structural inequalities, the motivation and perceived capacity to effect change, and social action to redress inequity. A wave of recent instruments measuring critical consciousness has been rigorously validated. Yet, whether these measures efficiently assess different levels of critical consciousness or contain redundant, or non-informative, items remain unknown. This research develops a short version (Short CCS, or ShoCCS) of the previously validated Critical Consciousness Scale. Using Item Response Theory methods, the long-form CCS is scrutinized for redundant items to efficiently measure critical reflection, critical motivation, and critical action. The resulting 13-item ShoCCS yields an internally consistent instrument with similar information distributions as the longer measure. Since the ShoCCS places less financial and time burden on investigators and respondents in comparison to the original CCS, and includes a new measure of critical motivation, it may streamline CC measurement in scholarship, practice, and policy.